Effects of Physical Exercise Interventions on Dual-Task Gait Speed Following Stroke: A Systematic Review and Meta-Analysis - Plummer, Prudence; Iyigun, Gozde (W B Saunders Co-Elsevier Inc, 2018)
Objectives: To estimate the treatment effects of exercise and/or gait training interventions on dual task walking in people with stroke. The secondary objective was to conduct subgroup analyses to compare the treatment effects of interventions involving dual task training to those without any dual task training. Data Sources: A systematic search of the literature was conducted in 6 databases (PubMed, CINAHL, EMBASE, Web of Science, Cochrane Central Register of Controlled Trials, and Physiotherapy Evidence Database) up to July 18, 2017. Study Selection: Randomized controlled trials (RCTs), nonrandomized controlled trials, or uncontrolled studies involving individuals with stroke and examining the effects of exercise and/or gait training interventions on dual task gait speed. Data Extraction: We extracted data on participant characteristics, intervention duration, frequency, and type; pre and post gait speed and secondary nongait task performance for single and dual task conditions, types of tasks used for dual task assessment and dual task prioritization instructions. Data Synthesis: Of 313 articles identified, 7 studies involving 12 independent treatment arms (n=124) met the inclusion criteria. There was a significant pre-post intervention increase in dual-task gait speed (MD: 0.03m/s, 95% CI: 0.01, 0.06) and single-task gait speed (MD: 0.06m/s, 95% CI: 0.03, 0.09). Dual-task training tended to have a larger effect on dual-task gait speed than interventions without dual-task training. Between-group analysis of three RCTs found evidence of superiority of dual-task gait training over single-task gait training for improving dual task gait speed (MD: 0.08m/s, 95% CI: 0.02, 0.14). Conclusions: Exercise and gait training interventions, especially those involving dual task practice, may improve dual task gait speed after stroke, but the clinical significance is unclear. Current effect size estimates lack precision due to small sample sizes of existing studies. (C) 2018 Published by Elsevier Inc. on behalf of the American Congress of Rehabilitation Medicine.
Keywords: Attention; Gait; Rehabilitation; Stroke; Walking speed